(untitled) (Dhaka University Journal of Science, 2022)
Electrochemistry at the interface between two immiscible electrolyte solutions (ITIES) has become an important and powerful platform for the detection and characterization of a wide variety of organic and inorganic species. Liquid/liquid electrochemistry overcomes some limitations faced in conventional solid/liquid electrochemistry. These include employment ofion transfer voltammetry across the ITIES as the basis for detection of non-redoxactive ions. The analytical sensitivity increasedon miniaturisation of the interface with an improvement insensitivity due to the enhanced mass transport via convergent diffusionas the size of the ITIES is minimised. In this review article, the ITIES is briefly described along with the scope of electrochemical research at micro-ITIES. Dhaka Univ. J. Sci. 69(3): 186-193, 2022 (June)